Early Warning System Melalui Edukasi Pra, Intra dan Pasca Bencana Di Wilayah Kerja Puskesmas Cinambo - Nurlianawati, Lia; Dirgahayu, Inggrid; Vitniawati, Vina; Sumbara, Sumbara (Yayasan Inspirasi El Burhani, 2024)
Introduction: Early warning systems are an effective way to minimize the impact of disasters. It provides information on the potential occurrence of natural disasters and the steps that communities should take. However, in many areas, community knowledge and understanding of this system is still minimal Objective: The purpose of this service was to increase the community's understanding of how to properly respond to disaster signs and improve community preparedness for disasters. Method: This public service was conducted by lecturers and students of the faculty of nursing, Bhakti Kencana University. Result: Before the activity, most of the community knowledge, namely 28 people (80%) had less knowledge about pre, intra and post disaster mitigation, while after the activity, most of the 33 people (100%) of the community could explain and be able to perform BHD simulations and simple wound care Conclusion: The community experienced a significant increase in knowledge on how to respond to early warning of disasters, as well as evacuation procedures to be taken. The disaster simulation on basic life support and simple wound care that was conducted showed that most of the community members (100%) were able to follow the procedures well